Peran Orangtua dalam Melatih Keterampilan Sosial pada Remaja dengan Autisme - Maharani Dinda Kallista; Lena N. Panjaitan; Aniva Kartika (Universitas Muhammadiyah Jember, 2020)
Adolesscent with Autism Spectrum Disorder (ASD) tend to be ostracized and bullied in school because they have fewer social skills. Though social skills can be improved, even though ASD teens will have certain challenges. Therefore the role of parents is very important in improving their social skills. This research was conducted to see how the description of social skills possessed by ASD adolescents, viewed from an internal process consisting of three aspects namely emotional awareness and understanding, a theory of mind, and problem-solving and how the role of parents in training social skills in them. Participants in this study were two mothers from mild ASD adolescents. Methods of data collection through interviews, open questionnaires, and four measuring instruments (Karolinska Directed Emotional Face test, Faux Pas Stories Test, Problem Solving Questionnaire, and Recognizing and Responding to a Problem Situation Assessment). The results of this study indicate that the role of parents in practicing social skills in ASD adolescents has not shown optimal results, as evidenced by the lack of social skills possessed by ASD adolescents and the social problems they face in school.